ANALYSIS OF JANUARY EFFECT ON BIG STOCK COMPANIES AND SMALL STOCK COMPANIES AT INDONESIA STOCK EXCHANGE - Addinpujoartanto, Nur Ariefin (Universitas Teknologi Yogyakarta, 2019)
January Effect is one of market anomaly where the stock returns in January are higher than other months. Some of causes the January Effect are the actions of investor who carry out tax-loss selling and windows dressing. In addition, investors have different views to choose stocks, based on market capitalization dan risk. This study is purposed to find the January Effect in the Indonesia Stock Exchange and January Effect on small company stock is stronger than large company stock. The data is normally distributed using the One-Sample Kolmogorov-Smirnov test. The test using the OLS method with dummy variable at five percent significance level. By using a sample of 30 large company stocks and 30 small company stocks based on market capitalization during period 2013-2017, the result of this study found a January Effect in the Indonesia Stock Exchange. But the January Effect doesn?t occur on small company stock, except on large company stock during that periode.